TINGKAT KETAHANAN DIRI TERHADAP PENYALAHGUNAAN NARKOBA PADA MAHASISWA PRODI S1 STF MUHAMMADIYAH CIREBON DENGAN ANTI DRUG SCALE - Rahmi Nurhaini; Sidik Lingga Kusuma; Yuniarti Falya; Dahlia Nur Rahmawati; Ayu Mulyani; Tomi (Universitas Muhammadiyah Klaten, 2024)
Drug abuse is the act of using drugs without rights or against the law. Drug abuse can be caused by internal or external factors within a person. This research aims to see a picture of a person's level of resistance to drug abuse among students of the STF Muhammadiyah Cirebon undergraduate study program. In this research, a prospective observational study was carried out using the ADS (Anti-Drug Scale) questionnaire which was validated in Google form on 95 level II undergraduate study program students as respondents. The results of this research show that the number of female respondents is greater than male, namely 81.05%. Most respondents were 20 years old, namely 57.89%. The values for the three ADS dimensions (Anti-Drug Scale) obtained from the questionnaire results showed a percentage of 41.20% in the healthy dimension, 71.84% in the conscious dimension, and 57.37% in the productive dimension. With an average value of self-resilience (anti-drugs) in the three dimensions of 56.80%. So undergraduate study program students have a very high level of self-resilience which can mean that STF Muhammadiyah Cirebon undergraduate study program students have good abilities so they can avoid the effects of drug abuse. Keywords: Drugs; Personal Resilience; STF Muhammadiyah Cirebon student